Work life balance and job satisfactions / Muhammad Asyraf Su’eb - Su’eb, Muhammad Asyraf (Faculty of Business and Management, 2019)
Job satisfaction could simply be defined as how employees feel about their jobs. Thus, in view of the importance of work-life balance, this study examined its role to influence towards employee job satisfaction. A sample of 145 respondents is collected from healthcare service provider in Muar. Based on results, it was found social support and motivation (H2 and H4) have significant relationship towards job satisfaction. Meanwhile, working environment and work family conflict (H1 and H3) showed no significant relationship towards employee job satisfaction. The results of the study verify it is vital for organizations to critically reevaluate and improvise the policy, process and standard operating procedure that will influence crucially towards employee job satisfactions. For future research we suggest to add more dimensions of job satisfaction and to widen the group of the population for more rigorous findings.